Development of Physics Practicum Module with Scientific Approach on Dynamic Fluid Material at SMAN 2 Medan - Friska Hariyani; Yuni Warty (Journal of Learning and Technology in Physics, 2024)
This research is based on problems that occur at SMA Negeri 2 Medan where the school does not have a practicum module, especially in physics learning. This study aims to develop a physics practicum module with scientific approach on dynamic fluid material and analyze the validity of practicum modules in terms of the level of validity, practicality, and effectiveness of the module. The type of research used is Research and Development (R&D) which refers to the ADDIE model. The data collection technique is in the form of validity questionnaire, practicality questionnaire and module effectiveness questionnaire in the form of pre-test and post-test questions. This research was conducted through the stages of analysis, design, development, implementation and evaluation. The subjects of this study included two physics lecturers and physics teachers as validators, as well as students of class XI Mipa 1 SMA Negeri 2 Medan. The results of the study in the form of module validity level which obtained an average of 92.2% with a very valid category, the module practicality level obtained an average of 89.9% with a very practical category. Meanwhile, the effectiveness level of the module obtained N-gain of 0.65 which shows there is an increase in student learning outcomes seen from the pre-test and post-test results. The level of effectiveness of the physics practicum module with scientific approach on dynamic fluid material is declared valid, practical, and effective. Keywords: Practicum Module; Scientific Approach; Dynamic Fluid